Knight-Walras equilibria - Patrick Beißner; Frank Riedel (Bielefeld University, Center for Mathematical Economics (IMW), 2016)
Knightian uncertainty leads naturally to nonlinear expectations. We introduce a corresponding equilibrium concept with sublinear prices and establish their existence. In general, such equilibria lead to Pareto inefficiency and coincide with Arrow-Debreu equilibria only if the values of net trades are ambiguity-free in the mean. Without aggregate uncertainty, inefficiencies arise generically. We introduce a constrained efficiency concept, uncertainty-neutral efficiency and show that Knight-Walras equilibrium allocations are efficient in this constrained sense. Arrow-Debreu equilibria turn out to be non-robust with respect to the introduction of Knightian uncertainty.
urn:nbn:de:0070-pub-29035383
Keywords: D81; C61; G11; 330; Knightian Uncertainty; Ambiguity; General Equilibrium